INVESTIGATIVE COLLECTED POEMS OF HASAN ASAPAHANI FROM FIGURATIVE AND SEMANTIC PERSPECTIVE - Husni Thamrin; Arif Muhammad (Institut Pendidikan Indonesia Garut, 2019)
This study is purposed to analyze the ten of collected poems â€œLelaki yang Dicintai Bidadariâ€. It is primarily to find out the figurative language thatâ€™s being used in the poem and also to figure out the poem meaning semantically. This study used descriptive and qualitative approach based on the view of its procedural frame which are planning, implementation, analyzing, finding, and reporting. There are six types of figurative language used on some of Hasan Aspahani's poems. The six types of figurative language are found based on the data used in the collection of Hasan Aspahani's poems, there are hyperbole, irony, metaphor, personification, antithesis, and symbol. The conclusion that can be taken from the data source is that the most commonly figurative language which used in the poems of Hasan Aspahani is Metaphor. From the semantic meaning interpretation result, it is expected that the majority of poemsâ€™ words are in connotative since the author mostly use metaphor in expressing romantic poems